Pengaruh Perceived Overqualification, Emotional Exhaustion terhadap Spiritual Wellbeing Melalui Variabel Mediator Cyberloafing pada Karyawan Gen Z - Rezi Dwi Astuti; Netania Emilisa; Mutia Nurhikmah; Fatieha Rizqillah (Syntax Corporation Indonesia, 2024)
This study analyzes the influence of Perceived Overqualification and Emotional Exhaustion on Spiritual Wellbeing mediated by Cyberloafing on Gen Z employees in insurance sector companies in Jakarta. Data was collected through a survey using an online questionnaire with a purposive sampling method. This study uses descriptive statistical analysis and Structural Equation Modeling (SEM) to test the hypothesis. The results showed that Emotional Exhaustion had a significant influence on Cyberloafing, while Perceived Overqualification did not show a significant relationship with Cyberloafing. In addition, Cyberloafing does not mediate the relationship between Perceived Overqualification and Spiritual Wellbeing. This research provides insight into the importance of employee welfare management to increase productivity and mental stability in the work environment.